Development Of Structurally Enhanced Air-Dried Rice Flour-Soy Protein Isolate Noodles - Ojukwu, Moses (2022)
Rice flour noodle is gluten-free, with excellent nutritional properties, but the lack of the functionality of forming a continuous visco-elastic dough contributes to rice flour noodles' poor texture. Fresh rice noodles have a short shelf life and are prone to spoilage due to high moisture content. However, air-dried rice noodles have been reported to shrink while processed and have poor rehydration characteristics. This research aimed to develop a structurally enhanced air-dried rice flour-soy protein isolate noodle. Firstly, fresh rice flour-soy protein isolate noodles (RNS) were developed to match those of yellow alkaline noodles (YAN) by incorporating microbial transglutaminase (RNS-MTG), glucono-δ- lactone (RNS-GDL), and both MTG and GDL into the RNS noodles (RNS-COM). After that, the central composite design of response surface methodology was employed to optimize the inclusion of soy protein isolate (SPI), microbial transglutaminase (MTG), and glucono-δ-lactone (GDL), after which sensory evaluation was carried out. This was followed by investigating the effects of steaming for 5 (S5) or 10 (S 10) min during the preparation of air-dried RNS-COM-S5 and RNS-COM-S10, respectively. Next, RNS-COM was dried using superheated steam (SHS) to yield RNS-COM-SHS. The formation of γ-glutamyl-lysine bonds in RNS-COM and RNS-MTG was shown by Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis analysis. Scanning Electron Microscope showed that compared to others, the structure of RNS-COM was denser, smoother with extensive apparent interconnectivity of aggregates.